Commercialization of Cultural Tourism and its Impact on the Authenticity and Preservation of Local Wisdom - Muda, Florianus Pruda (CV. Media Digital Publikasi Indonesia, 2026)
This study conducts a systematic literature review to analyze the complex relationship between the commercialization of cultural tourism and its influence on authenticity and the preservation of local wisdom from both theoretical and managerial perspectives. By synthesizing findings from ten selected articles published between 2000 and 2025, the study investigates how commercialization, through the process of commodification, poses challenges to cultural integrity while simultaneously providing opportunities for preservation. The analysis reveals that the success of commercialization in maintaining authenticity and sustainability is mediated by multiple factors, including community participation, legal protection, effective destination management, and the integration of digital innovation. The study further emphasizes the managerial importance of stakeholder collaboration and community-based governance as key mechanisms to harmonize market objectives with cultural values. Synthesizing these insights, a Community-Based Cultural Commercialization (CBCC) framework is proposed, integrating three managerial pillars: community empowerment, digital co-creation, and institutional governance. This framework strengthens the practical and theoretical understanding of sustainable cultural tourism, offering strategic guidance for policymakers, destination managers, and cultural institutions in balancing economic goals with the preservation of local wisdom.